EFEKTIVITAS MEDIA PASIR SILIKA DAN KARBON AKTIF TEMPURUNG KELAPA SEBAGAI MEDIA FILTRASI DALAM MENURUNKAN BOD DAN COD PADA LIMBAH LAUNDRY - Susanti, Arnila; Khair, Abdul; Syarifudin A; Haris, Abdul (Cahaya Ilmu Bangsa Institute, 2024)
Effectiveness Of Silica Sand Media and Coconut Shell Activated Carbon As Filtration Media In Reducing BOD and COD In Laundry Waste. Laundry waste is the remaining waste water resulting from the process of washing clothes. Laundry waste contains BOD and COD contamination indicator. In this research, liquid waste was processed using silica sand and coconut shell activated carbon. This aim of this study was to determine the effectiveness of silica sand filter media and coconut shell activated carbon as filtration media in reducing BOD and COD levels in laundry waste. This research was True Experimental with a Posttest Only Control Group Design with control and treatment of variations in the thickness of silica sand, namely 0 cm, 20 cm, 25 cm and 30 cm. The results of the Kruskal Wallis test showed that there was a difference between the thickness of 0 cm, 20 cm, 25 cm and 30 cm of silica sand in reducing BOD levels and the results of the Mann-Whitney test showed that a thickness of 30 cm is effective in reducing BOD levels. .One Way Anova test results showed differences between the thickness of 0 cm, 20 cm, 25 cm and 30 cm of silica sand in reducing COD levels and the results of Post Hoc Tests showed that a thickness of 30 cm was effective in reducing COD levels.The suggestion for future researchers is that it is necessary to increase the thickness of silica sand and coconut shell activated carbon in order to reduce BOD and COD levels in accordance with quality standards. Efektivitas Media Pasir Silika dan Karbon Aktif Tempurung Kelapa Sebagai Media Filtrasi dalam Menurunkan BOD dan COD pada Limbah Laundry. Limbah laundry merupakan sisa air buangan hasil dari proses kegiatan pencuician pakaian. Limbah lauindry meinganduing indikator ceimaran BOD dan COD. Pada peineilitian ini dilakuikan peingolahan limbah cair meingguinakan meidia pasir silika dan karbon aktif teimpuiruing keilapa. Tuijuian peineilitian ini uintuik meingeitahuii eifeiktivitas filteir meidia pasir silika dan karbon aktif teimpuiruing keilapa seibagai meidia filtrasi dalam meinuiruinkan kadar BOD dan COD pada limbah lauindry.Peineilitian ini beirsifat Truiei Eixpeirimeintal deingan rancangan Possteist Only Control Grouip Deisign deingan kontrol dan peirlakuian variasi keiteibalan pasir silika yaitui 0 cm, 20 cm, 25 cm, dan 30 cm. Hasil uiji Kruiskal Wallis meinuinjuikkan teirdapat peirbeidaan antara keiteibalan pasir silika 0 cm, 20 cm, 25 cm, dan 30 cm teirhadap peinuiruinan kadar BOD dan hasil uiji Mann-Whitneiy meinuinjuikkan keiteibalan 30 cm eifeiktif dakam meinuiruinkan kadar BOD. Hasil uiji Onei Way Anova teirdapat peirbeidaan antara keiteibalan pasir silika 0 cm, 20 cm, 25 cm, dan 30 cm teirhadap peinuiruinan kadar COD dan hasil uiji Post Hoc Teists meinuinjuikkan keiteibalan 30 cm eifeiktif dalam meinuiruinkan kadar COD. Saran bagi peineiliti seilanjuitnya adalah peirlui dilakuikan peinambahan keiteibalan pasir silika dan karbon aktif teimpuiruing keilapa agar dapat meinuiruinkan kadar BOD dan COD seisuiai deingan standar bakui muitui.